2014
DOI: 10.1103/physrevlett.113.068303
|View full text |Cite
|
Sign up to set email alerts
|

Sharp and Fast: Sensors and Switches Based on Polymer Brushes with Adsorption-Active Minority Chains

Abstract: We propose a design for polymer-based sensors and switches with sharp switching transition and fast response time. The switching mechanism involves a radical change in the conformations of adsorption-active minority chains in a brush. Such transitions can be induced by a temperature change of only about ten degrees, and the characteristic time of the conformational change is less than a second. We present an analytical theory for these switches and support it by self-consistent field calculations and Brownian … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
82
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 56 publications
(84 citation statements)
references
References 22 publications
(30 reference statements)
0
82
2
Order By: Relevance
“…The switching time is one major issue for the quality of sensors or other responsive materials. In our previous work [17], we performed overdamped Brownian dynamics simulations of a single switch chain in a static brush potential to estimate the switching time. By tracking the position of the free end bead of the minority chain, we found that this bead could jump between two well separated positions (which correspond to the exposed and adsorbed state, respectively) during a time about 10 6 τ mono , where τ mono is the characteristic relaxation time of a single monomer, which is typically on the order of 10 −9 seconds for flexible chains.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
See 3 more Smart Citations
“…The switching time is one major issue for the quality of sensors or other responsive materials. In our previous work [17], we performed overdamped Brownian dynamics simulations of a single switch chain in a static brush potential to estimate the switching time. By tracking the position of the free end bead of the minority chain, we found that this bead could jump between two well separated positions (which correspond to the exposed and adsorbed state, respectively) during a time about 10 6 τ mono , where τ mono is the characteristic relaxation time of a single monomer, which is typically on the order of 10 −9 seconds for flexible chains.…”
Section: Conclusion and Remarksmentioning
confidence: 99%
“…IV presents a more detailed derivation of the theory for the adsorption-active minority chain sketched in Ref. [17]. In Sec.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, scientists are now turning increasingly interested in their vital roles in biological systems [5][6][7]. Apart from that, branched polymers offer a large number of free ends that may be functionalized, serving in nano-technical applications such as environment-responsive surface layers [8][9][10][11][12][13][14], or as antifouling barriers [15][16][17] on sensitive surfaces. When grafted onto colloids, they lead to an improved stability against coagulation, featuring a thinner polymeric layer than colloids decorated with linear chains [18].…”
Section: Introductionmentioning
confidence: 99%